The global economic crisis: Long-term unemployment in the OECD - P. N. Raja Junankar (Institute for the Study of Labor (IZA), 2011)
This paper analyses the impact of the global economic crisis on unemployment and long term unemployment in the OECD. It uses simple econometric models using panel data (quarterly) and time series data. In general, we find that long term unemployment increases with the unemployment rate, there is persistence in long term unemployment, and that the employment protection variable and the replacement rate are statistically insignificant. Overall, the findings of our research are that there are many differences between the impact of the Great Recession on different countries. Countries that faced a significant financial crisis and a collapse of the housing market bubble have had large increases in unemployment and long term unemployment. There was a big fall in employment in the (especially) construction and manufacturing industries. The financial collapse led to an increase in unemployment in the financial and business sector. As a result of these twin shocks labour mobility of the unemployed is likely to be affected: with negative equity in housing, unemployed workers are unlikely to move regionally. With a loss of wealth (in housing and financial assets, including superannuation) there will be a fall in consumer spending which will slow down the recovery of economies. This means that, especially for some countries, there will be a long period of high unemployment and long term unemployment.
urn:nbn:de:101:1-201111072659
Keywords: E24; J60; J68; J69; 330; long-term unemployment; global crisis; labour market policies; OECD; Wirtschaftskrise; Langzeitarbeitslosigkeit; Finanzmarktkrise; Immobilienmarkt; Bubbles; Schätzung; OECD-Staaten